Geomorphological Hazards and Disaster Prevention - Goudie, Andrew S (aCambridge Cambridge University Press, 2010)
Human activities have had a huge impact on the environment and landscape, through industrialisation and land-use change, leading to climate change, deforestation, desertification, land degradation, and air and water pollution. These impacts are strongly linked to the occurrence of geomorphological hazards, such as floods, landslides, snow avalanches, soil erosion, and others. Geomorphological work includes not only the understanding but the mapping and modelling of Earth's surface processes, many of which directly affect human societies. In addition, geomorphologists are becoming increasingly involved with the dimensions of societal problem solving, through vulnerability analysis, hazard and risk assessment and management. The work of geomorphologists is therefore of prime importance for disaster prevention. An international team of geomorphologists have contributed their expertise to this volume, making this a scientifically rigorous work for a wide audience of geomorphologists and other Earth scientists, including those involved in environmental science, hazard and risk assessment, management and policy.
Electronic reproduction.
Keywords: Natural disasters; Geomorphology; Hazardous geographic environments; Hazardous geographic environments -- Risk assessment; Natural disasters -- Prevention